KAJIAN ESTETIKA IMPLEMENTASI BAMBU LAMINASI PADA TRANSFORMABLE FURNITURE BRUNA CABINET - Eilsa Adelia; Sany, Nukhbah; Damastuti, Prasiska; Damayanti, Friska; Ma’Wa, Safarah Putri (Indonesian Society of Applied Science, 2024)
The limitation of wood as a raw material for furniture production has prompted researchers to seek non-wood alternative materials. Among these alternatives, bamboo has been utilized for furniture production. However, the bamboo used is typically in its whole form, which restricts the types and shapes of furniture that can be produced. Using the design thinking method, starting from the empathize, define, ideate, prototype, and test stages, the goal of this research was to explore the aesthetic value of a cabinet that can transform from one function to another using processed bamboo material—specifically, vertically laminated bamboo with grooves. Data collection involved initial questionnaires distributed to potential users, interviews with bamboo processing industry practitioners, and a literature review of books, journals, and internet articles. The final outcome of this study is a working drawing and a prototype cabinet made from laminated bamboo material that can transform into a writing desk. Respondent evaluations indicated that the prototype was 71.39% comfortable (Good) and had an average aesthetic rating of 84.125%. Additionally, 33% of respondents expressed interest in purchasing the prototype at the specified price.